Eruptive Facial Postinflammatory Lentigo: Clinical and Dermatoscopic Features. (November 2016) - Cabrera, Raul; Puig, Susana; Larrondo, Jorge; Castro, Alex; Valenzuela, Karen; Sabatini, Natalia
Abstract : Abstract: The face has not been considered a common site of fixed drug eruption, and the authors lack dermatoscopic studies of this condition on the subject. The authors sought to characterize clinical and dermatoscopic features of 8 cases of an eruptive facial postinflammatory lentigo. The authors conducted a retrospective review of 8 cases with similar clinical and dermatoscopic findings seen from 2 medical centers in 2 countries during 2010–2014. A total of 8 patients (2 males and 6 females) with ages that ranged from 34 to 62 years (mean: 48) presented an abrupt onset of a single facial brown-pink macule, generally asymmetrical, with an average size of 1.9 cm. after ingestion of a nonsteroidal antiinflammatory drugs that lasted for several months. Dermatoscopy mainly showed a pseudonetwork or uniform areas of brown pigmentation, brown or blue-gray dots, red dots and/or telangiectatic vessels. In the epidermis, histopathology showed a mild hydropic degeneration and focal melanin hyperpigmentation. Melanin can be found freely in the dermis or laden in macrophages along with a mild perivascular mononuclear infiltrate. The authors describe eruptive facial postinflammatory lentigo as a new variant of a fixed drug eruption on the face.